Noise and vibration analysis : signal analysis and experimental procedures - Brandt, Anders (Chichester ; Hoboken, N.J. : Wiley, 2011)
"Noise and Vibration Analysis adopts a practical learning approach, building upon two existing class-note type books that have been used by the author for 10 years of teaching two academic courses"--
Front Matter -- Introduction -- Dynamic Signals and Systems -- Time Data Analysis -- Statistics and Random Processes -- Fundamental Mechanics -- Modal Analysis Theory -- Transducers for Noise and Vibration Analysis -- Frequency Analysis Theory -- Experimental Frequency Analysis -- Spectrum and Correlation Estimates Using the DFT -- Measurement and Analysis Systems -- Rotating Machinery Analysis -- Single-Input Frequency Response Measurements -- Multiple-Input Frequency Response Measurement -- Orthogonalization of Signals -- Advanced Analysis Methods -- Appendix A: Complex Numbers -- Appendix B: Logarithmic Diagrams -- Appendix C: Decibels -- Appendix D: Some Elementary Matrix Algebra -- Appendix E: Eigenvalues and the SVD -- Appendix F: Organizations and Resources -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Vibration -- Mathematical models; Noise -- Mathematical models; Acoustical engineering; Stochastic analysis; Signal processing; TECHNOLOGY & ENGINEERING -- Drafting & Mechanical Drawing; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Acoustical engineering; Noise -- Mathematical models; Signal processing; Stochastic analysis; Vibration -- Mathematical models; Electronic books